2010
DOI: 10.1603/ec10018
|View full text |Cite
|
Sign up to set email alerts
|

Activity of <I>Bacillus thuringiensis</I> Isolates Against Immature Horn Fly and Stable Fly (Diptera: Muscidae)

Abstract: We screened 85 isolates of Bacillus thuringiensis (Berliner), making up 57 different subspecies, and two isolates of Bacillus sphaericus (Meyer and Neide) for activity against immature horn flies, Haematobia irritans (L.), and stable flies, Stomoxys calcitrans (L.). The majority of B. thuringiensis and the B. sphaericus isolates had little or no activity against horn fly and stable fly. Approximately 87% of the isolates caused < 50% mortality of horn fly larvae and 64% caused < 25% mortality. For stable fly, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Five isolates of B. thuringiensis were used that had previously shown activity against stable ßy (Lysyk et al 2010 Bacterial Spore Cultures. Bacterial isolates were cultured separately in medium containing 8 g/liter nutrient broth (BD Biosciences, Cockeysville, MD), 2-mM MgSO 4 , 1-mM CaCl 2 , 10 Ϫ5 -M MnCl 2 , and 10 Ϫ6 -M FeSO 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five isolates of B. thuringiensis were used that had previously shown activity against stable ßy (Lysyk et al 2010 Bacterial Spore Cultures. Bacterial isolates were cultured separately in medium containing 8 g/liter nutrient broth (BD Biosciences, Cockeysville, MD), 2-mM MgSO 4 , 1-mM CaCl 2 , 10 Ϫ5 -M MnCl 2 , and 10 Ϫ6 -M FeSO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we identiÞed several isolates of Bacillus thuringiensis that have activity against larval stable ßies (Lysyk et al 2010). These isolates included B. t. tolworthi 4L3,B.…”
mentioning
confidence: 99%
“…Early research with exotoxin-producing strains of B. thuringiensis was promising, but the shift in emphasis to endotoxin-only strains with high activity against Lepidoptera limited discovery of fly-active strains (1,36,50). Surveys have suggested that strains with high levels of the Cry1B endotoxin are more virulent than other strains for muscoid flies (37). Recent successes with B. thuringiensis var.…”
Section: Cypoviruses Are Also Referred As Cytoplasmic Polyhedrosis VImentioning
confidence: 99%
“…Several reports have indicated activity against tick species as well (Zhioua et al 1999, Fernández-Ruvalcaba et al 2010. Recently, we have reported on several isolates that have activity against immature stable ßy (Lysyk et al 2010, Lysyk andSelinger 2012). Because these isolates have already shown activity against immature stable ßies, we conducted the current study to examine whether they had activity against adult stable ßy.…”
mentioning
confidence: 96%